Plant defense inducers and antioxidant metabolites produced during oil palm-ganoderma boninense interaction in vitro - Shokrollahi, Neda; Ho, Chai-Ling; Mohd Zainudin, Nur Ain Izzati; Abdul Wahab, Mohd As’wad Bin; Wong, Mui-Yun (Springer Science, 2023)
Ganoderma boninense Pat. has been recognized as a white rot pathogenic fungus and the causal agent of basal stem rot (BSR) in oil palm. BSR is a destructive disease which has threaten oil palm without any efective treatment available until now. This study analyzed extracellular metabolites secreted by G. boninense during the interaction with oil palm plantlets in vitro using Liquid Chromatography with Tandem Mass Spectrometry (LC–MS/MS) and Gas Chromatography Mass Spectrometry (GC–MS). Roots of three months old oil palm plantlets were artifcially inoculated with G. boninense. After 14 days, metabolites released by G. boninense in the environment compared to samples without plantlets (as control) were extracted using ethyl acetate. LC–MS/MS analysis identifed azelaic acid (AzA), isonicotinic acid (INA), and ricinoleic acid (RA) in the negative polarity while none was identifed in the positive ion mode. In the control sample, α-ketoisovaleric acid was identifed in the negative polarity mode. Identifcation of RA produced by G. boninense, as a frst report, provides a basis for more extensive studies on sclerotia production and its role in BSR pathogenesis. GC–MS analysis detected a total of 51 bioactive compounds in the crude extract containing interaction of Ganoderma-oil palm and demonstrated high amount of phenol with one aromatic ring (64) and 5-Hydroxymethyl-1,1,4a-trimethyl-methylenedecahydronaphthalen-2-ol (14), respectively. This study presents a new perspective regarding the secondary metabolites involved during the interaction of G-boninense and oil palm roots.